2018
DOI: 10.22435/vk.v10i1.969
|View full text |Cite
|
Sign up to set email alerts
|

Identifikasi Hewan Reservoir Leptospirosis Di Daerah Peningkatan Kasus Leptospirosis Di Desa Pagedangan Ilir, Kecamatan Kronjo, Kabupaten Tangerang Tahun 2015

Abstract: In Indonesia, leptospirosis often causes outbreaks. Three important sources of transmission of leptospirosis are the environment contaminated with leptospira, the presence of rats and presence of livestock as reservoirs. This study aims to determine the reservoir that plays a role in the leptospirosis transmission in increased case areas of leptospirosis in the Pagedangan Ilir Village, Kronjo Sub-district, Tangerang. Rat traping was done twice. Each trapping was done two times, in consecutive days. Livestock s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 6 publications
0
5
2
2
Order By: Relevance
“…9[in review] Meanwhile, the previous research by Joharina et al (2019) showed the prevalence of L. interrogans in Bantul Regency was 20.4%. 33 The prevalence of L. interrogans in this research was higher than Romadhona's research but a little lower than Joharina's. 9,33 This research was conducted at several areas of Yogyakarta City and Sleman, thus can be said that prevalence of L. interrogans in several areas of Sleman and Yogyakarta City was higher than in four District of Yogyakarta City, but lower than in Bantul Region.…”
Section: Identification Distribution and Trap Success Of Collected Ra...contrasting
confidence: 68%
See 1 more Smart Citation
“…9[in review] Meanwhile, the previous research by Joharina et al (2019) showed the prevalence of L. interrogans in Bantul Regency was 20.4%. 33 The prevalence of L. interrogans in this research was higher than Romadhona's research but a little lower than Joharina's. 9,33 This research was conducted at several areas of Yogyakarta City and Sleman, thus can be said that prevalence of L. interrogans in several areas of Sleman and Yogyakarta City was higher than in four District of Yogyakarta City, but lower than in Bantul Region.…”
Section: Identification Distribution and Trap Success Of Collected Ra...contrasting
confidence: 68%
“…33 The prevalence of L. interrogans in this research was higher than Romadhona's research but a little lower than Joharina's. 9,33 This research was conducted at several areas of Yogyakarta City and Sleman, thus can be said that prevalence of L. interrogans in several areas of Sleman and Yogyakarta City was higher than in four District of Yogyakarta City, but lower than in Bantul Region. The high result in prevalence of L. interrogans from this research can be considered as the presence of more L. interrogans in the collected rats and lead to higher potential transmission of leptospirosis.…”
Section: Identification Distribution and Trap Success Of Collected Ra...contrasting
confidence: 68%
“…The study of Joharina et al in 2018 showed the percentage of positive Leptospira rats of 30.8% [10]. Leptospira infection in R. norvegicus was 41.1% and in R. tanezumi was 11.1%.…”
Section: Advances In Health Sciences Research Volume 24mentioning
confidence: 94%
“…The study was carried out on October to November 2015 in Kronjo Village, Tangerang Regency, Banten (Picture 1). In 2015, there was an increase in leptospirosis cases in the study site [10]. Rats were trapped by using 100 live traps in two consecutive days.…”
Section: Methodsmentioning
confidence: 99%
“…Beberapa penelitian di Kota Semarang, Boyolali, Pati, Banyumas, Tangerang, dan Maumere menunjukkan bahwa jenis tikus yang terpapar Leptospira didominasi oleh kedua jenis tikus tersebut dengan angka prevalensi yang bervariasi. [30][31][32][33][34][35][36] Ditemukannya B. indica positif Leptospira di lokasi penelitian menunjukkan bahwa jenis tikus inilah yang kemungkinan besar berperan sebagai hewan reservoir Leptospira di lokasi tersebut, meskipun demikian peran hewan mamalia lain sebagai reservoir juga belum diketahui secara pasti.…”
Section: Pembahasanunclassified